Investigation of kidney function changes in sea salt workers during harvest season in Thailand - Titaporn Luangwilai; Mark Gregory Robson; Wattasit Siriwong (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. The Thai government has been developing its Eastern Economic Corridor (EEC), which spans three provinces, with the aim of improving connections with other Asian nations. Since this strategic development, the number of trucks, private car, and passenger car registrations have continued to grow, with a corresponding increase in related to benzene, toluene, ethylbenzene, and xylene (BTEX). Objectives. This study aims to compare the levels of trans, trans-muconic acid (t, t MA); toluene (TU); mandelic acid (MA); and methyl hippuric acid (MHA) in the urine of gas station employees, considering demographic and occupational factors. Material and methods. These employees worked either near or away from the fuel dispenser, and there 100 people in each group. Data were collected using interviews and testing environmental air and urine samples for benzene, toluene, ethyl benzene, and xylene (BTEX). Results. The results showed that BTEX concentrations were just detectable in all 200 cases (100%). The mean (±SD) urine level of t, t MA was 449.28 (±213.32) μg/g creatinine, while the median (min-max) was 428.23 (95.58-1202.56) μg/g creatinine. The mean TU was 0.011 (0.001) mg/L, while the median (min-max) was 0.011 (0.010-0.013) mg/L. MA levels were higher inside the pollution control zone than they were outside the zone (p=.009). Employees who practiced poor personal hygiene had relatively high urinary toluene and MHA levels (p=.009) and those who did not wear personal protective equipment (PPE) had relatively high MA levels (p=.040). Conclusion. The results of this study revealed statistically significant biomarkers influencing the levels of t, t MA; TU; MA; and MHA in urine. The recommendations of this study are that employers should provide their employees with suitable PPE, check regularly to ensure that it is worn, and strongly encourage employees to take care of their sanitation. Employees should take appropriate breaks and days off to minimize their exposure to BTEX.